MENINGKATKAN KINERJA PEGAWAI MELALUI EFIKASI DIRI DAN PERILAKU KERJA INOVATIF: MODEL MEDIASI - Mulyono, Deni Tri; Ilhami, Susanti Dwi; Rosyidi, Syaiko (CV. Denasya Smart Publisher, 2025)
This study aims to identify the relationship between self-efficacy and employee performance of ASN OPD Rembang District, Rembang Regency through innovative work behavior. The three variables are constructed and the relationship given between the three is seen. This study uses a descriptive quantitative method with data collection techniques using questionnaires and PLS-SEM as a tool for analyzing data. The sample of this study was 54 people with a total sampling method. Then, the data analysis stage was carried out by looking at the results of the evaluation of the outer model, inner model and conducting a model fit evaluation. Based on the data that has been processed using smartPLS version 4.1.1.2, a positive influence was found on each variable. Where the positive influence is seen in self-efficacy which has a significant positive effect on employee performance, self-efficacy which has a significant positive effect on employee innovative work behavior, and employee innovative work behavior has a significant positive effect on employee performance and innovative work behavior plays a significant role as a mediator in the influence of self-efficacy on employee performance. Therefore, it can be concluded that innovative work behavior can affect the relationship between self-efficacy and employee performance of ASN OPD Rembang District, Rembang Regency as partial mediation.